Determine the Outcome of Posterior Approach of Open Reduction and Internal Fixation in Supracondylar Type III Fracture in Children (Journal of Pakistan Orthopaedic Association, 2014)
Background: Supracondylar humeral fractures are the most common fractures seen in children. It is exclusively a fracture of immature skeleton. It has a greater rate of malunion, nerve injury, and poor results than any type of extremity fracture. Supracondylar type III fractures are recorded 54% in Pakistan. In situations where closed reduction fails, open reduction and k-wire fixation is applied.Objectives: To determine the outcome of posterior approach of open reduction and internal fixation in supracondylar type III fracture in children. Design: Descriptive case seriesResults: Majority of the patients 42%(n=42) were recorded between 6-10 years of age, 35%(n=35) were found with 11-14 years, and 23%(n=23) with 1-5 years. The mean age was recorded as 8.23 with 3.67 S.D. Gender distribution in the population included in our study, male were found in 71% (n=71) while females were found 29% (n=29). Status of loss of motion according to Flylnn’s criteria shows 58% (n=58) excellent, Good in 27% (n=27), while fair and poor were found in 15% (n=15). Regarding carrying angle according to Flylnn’s 63% (n=63) excellent, 26% (n=26) Good and 11% (n=11) were found with fair and poor outcome.Conclusion: Posterior approach of open reduction and internal fixation in supracondylar type III fracture in children regarding loss of motion and loss of carrying angle is successfulKey words: Supracondylar type III fracture, open reduction and internal fixation, posterior approach, loss of motion, loss of carrying angle